리튬 이온 전지용 망가니즈 기반 전환반응 음극 소재 - 이다영 (The Graduate School, Ajou University, 2024)
The prevailing electrode materials utilized in contemporary applications predominantly belong to intercalation-type, such as Li(NixCoyMn(1-x-y))O2 (NCM), LiFePO4 (LFP), and graphite. Despite their widespread application driven by high stability, intercalation-type materials encounter limitations in enhancing capacity due to their inherent charge-discharge mechanisms. [1] Consequently, there is a growing interest in conversion-type electrode materials as promising candidates for high-energy- density batteries. The appeal of conversion-type materials stems from their ability to store multiple moles of lithium ions per mole of the compound. This distinctive feature positions conversion-type electrodes as promising choices for next generation batteries. This research conducted a comparative study on Mn(OH)2 and Mn(OH)2/Mn3O4 composite, both classified as conversion-type electrode materials, to explore their potential as anode materials for next-generation batteries. The chemical and structural study via XRD, SEM, and TEM analysis confirmed that these materials formed hexagonal plates morphology, which is highly favorable characteristic for preparing additional composites with carbon materials such as graphene sheets. The lithium storage mechanisms on these materials were explored through ex-situ XRD and XPS analysis. The cascade reaction of lithium species, along with Mn metal formation, enables exceptional electrochemical performance. Mn(OH)2/Mn3O4 composite exhibits an impressive discharge capacity of ~2750 mAh g-1 in the initial cycle, significantly surpassing the theoretical capacities of both Mn(OH)2 and Mn3O4. This remarkable performance, exceeding that of bare hydroxide (~1527 mAh g-1), can be attributed to the presence of a small amount of Mn3O4, which improves reversible capacity and electrochemical reversibility. This study unveils the potential of Mn(OH)2/Mn3O4 composite as a high-performance anode material for next-generation batteries, showcasing the advancements that conversion-type electrode materials can bring new developments in battery technology.
학위논문(석사)--에너지시스템학과,2024. 2
Keywords: 리튬이온배터리; 음극; 전환반응 음극